2014
DOI: 10.1364/oe.22.025853
|View full text |Cite
|
Sign up to set email alerts
|

X-ray broadband Ni/SiC multilayers: improvement with W barrier layers

Abstract: We present an experimental study and performance improvement of periodic and aperiodic Ni/SiC multilayer coatings. Periodic Ni/SiC multilayer mirrors have been coated and characterized by grazing incidence X-ray reflectometry at 8.048 keV (Cu Kα radiation) and by measurements at 3 keV and 5 keV on synchrotron radiation facilities. An interdiffusion effect is found between Ni and SiC layers. A two-material model, Ni(x)Si(y)/SiC, using a silicide instead of Ni, was used to fit the measurements. The addition of 0… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 33 publications
0
3
0
Order By: Relevance
“…In the pure Ar coatings, the Si layer density is fixed to that of the nominal density of silicon in the LLNL database (2.33 g/cm 3 ). The NiV layers density are allowed to vary for all measurements, but expect to be near nominal density (8.79 g/cm 3 ), though B. Emprin et al 14 has reported Ni densities at 7.2 g/cm 3 at 8.0 keV. The silicon that is sputtered in a reactive Ar/N 2 atmosphere is varied, since it is reported to chemically change to silicon nitride which has a nominal density a 3.17 g/cm 3 .…”
Section: X-ray Reflectometry Characterizationmentioning
confidence: 99%
“…In the pure Ar coatings, the Si layer density is fixed to that of the nominal density of silicon in the LLNL database (2.33 g/cm 3 ). The NiV layers density are allowed to vary for all measurements, but expect to be near nominal density (8.79 g/cm 3 ), though B. Emprin et al 14 has reported Ni densities at 7.2 g/cm 3 at 8.0 keV. The silicon that is sputtered in a reactive Ar/N 2 atmosphere is varied, since it is reported to chemically change to silicon nitride which has a nominal density a 3.17 g/cm 3 .…”
Section: X-ray Reflectometry Characterizationmentioning
confidence: 99%
“…The current literature presents several material pairs investigated for applications in X-ray optics, including W/Si [4], Pt/C [5], Ni/SiC [6], Ir/B 4 C [7], W/B 4 C [8], and W/Sc [9]. Many authors observed interlayer mixing between the used pair materials, and have therefore involved separation/barrier layers from low-segregation materials.…”
Section: Introductionmentioning
confidence: 99%
“…Many authors observed interlayer mixing between the used pair materials, and have therefore involved separation/barrier layers from low-segregation materials. Emprin et al [6] used W to improve the X-ray reflectivity (XRR) of Ni/SiC multilayers. Although multilayer performance was not improved by the addition of W barrier layers, the authors showed very good agreement between modelled and experiment XRR results.…”
Section: Introductionmentioning
confidence: 99%